Pico Hydro Application for Off-Grid Settlement - Ab Razak, Juhari; MUSA@OTHMAN, MASJURI; Ayob, Md Razali; Hassan, Muhammad Zahir; Abd. Rahman, Md. Nizam; Sopian, Kamaruzzaman (2010)
Malaysia is currently constructing a large hydropower station with five more schemes under review. However these stations are catering for energy consuming industrial parks while the domestic supply is not making much in-road due to geographical constraints. This paper is discussing the use of off-grid alternative for power supply to the rural settlements. A run-of-river application, pico hydro, requires no dam or reservoir for water storage. It is intended for low flow and low head application. A mapping of possible locations for application along selected rivers in Malaysia is discussed. Two types of pico hydro turbine are selected for review and comparison in power production. Research are undertaken to promote this environment friendly technology to rural electrification program. Studies show that pico hydro manages to provide enough power for basic lighting needs in remote area where water is available with small drop or head.